Methods of learning and writing jawi scripts within the Malay community: Past and present experiences - Fadzli, Adam; Daud, Ismail; Asyraf, Ab Rahman; Abdul Manan, Ali (2017)
Jawi script is considered as the heritage of the Malay people and thus preserving and sustaining the script is vital since it shapes the identity of the Malays and their cultural heritage. This paper discusses some methods of learning and writing Jawi scripts within the Malay community and how the script writing system has gone through a systematic evolution through times due to requirements set by relevant authorities. Despite the latest development and evolution, the Jawi scripting system had played important roles as a medium to spread Islam, language development and Malay culture enhancements. Towards the end of the 20th century, the Jawi script began to fade away as it was gradually replaced by the Rumi (Roman or Latin alphabet) script that have a very strong influences in the education curriculum system. As a result, not many Malay younger generations know about Jawi alphabet yet again are unable to read or write in Jawi literature. These younger generations no longer fluent in Jawi literature compared to earlier days where everybody were Jawi literate regardless of their age category. Using qualitative research design involving content analysis of secondary data and interviews with selected informants amongst teachers and students of secondary schools, the study traced back the evolution of learning and writings Jawi script from past to the present days and demonstrated how different approaches were employed by those experts of Jawi scripts towards preserving the script and promoted its usage and interest amongst the Malay generation. The study found some approaches and techniques were successful at least at instilling interest amongst younger generations to write and read Jawi scripts including the introduction of a new learning method of Jawi script using the Latin alphabet called Rumi amongst school students.